2014
DOI: 10.1139/gen-2014-0110
|View full text |Cite
|
Sign up to set email alerts
|

DOP–PCR based painting of rye chromosomes in a wheat background

Abstract: To determine the appropriateness of chromosome painting for identifying genomic elements in rye, we microdissected the 1R and 1RS chromosomes from rye (Secale cereale L. var. King II) and wheat-rye addition line 1RS, respectively. Degenerate oligonucleotide primed - polymerase chain reaction (DOP-PCR) amplification of 1R and 1RS products from dissected chromosomes were used as probes to hybridize to metaphase chromosomes of rye, wheat-rye addition lines 1R and 1RS, translocation line 1RS.1BL, and allohexaploid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The DOP–PCR products of the smallest St chromosome from Tai‐27 only distributed in the pericentromeric region of St genome chromosomes (Deng et al, 2013a). In addition, the DOP–PCR products of 1R and 1RS yielded weaker signals in the terminals of chromosomes than in the other regions (Deng et al, 2014). The similar phenomemon could also be found in the chromosome painting of spinach ( Spinacia oleracea L.) using DOP–PCR products of microdissected Y chromosome as a probe (Deng et al, 2013b).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The DOP–PCR products of the smallest St chromosome from Tai‐27 only distributed in the pericentromeric region of St genome chromosomes (Deng et al, 2013a). In addition, the DOP–PCR products of 1R and 1RS yielded weaker signals in the terminals of chromosomes than in the other regions (Deng et al, 2014). The similar phenomemon could also be found in the chromosome painting of spinach ( Spinacia oleracea L.) using DOP–PCR products of microdissected Y chromosome as a probe (Deng et al, 2013b).…”
Section: Discussionmentioning
confidence: 92%
“…Deng et al (2013a) utilized the DOP‐PCR products of St‐genome chromosome to analyze the genomic constitution of Thinopyrum intermedium . They obtained the DOP–PCR products of chromosome 1R and 1RS using the same methods, and applied them to the identification of R genome chromosome in a wheat background (Deng et al, 2014). In this study, we obtained DOP–PCR products of chromosomes 6PS and 6PL and clearly identified chromosomes 6P, 6PS and 6PL in wheat– A. cristatum addition lines using them as probes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amplified products contain both high repetition and low copy sequences. Pich et al 1994, Hobza et al 2004, Deng et al 2014 Screening and identification of chromosomal microcloning Southern hybridization The genomic DNA labeled with certain markers hybridizes with the DNA library of the target chromosome/segment.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Nevertheless, the technique of chromosome microdissection and microcloning was successfully used in rye chromosomes by Saudery et al (1991), and the cloning of rye DNA was successfully achieved. Since then, the application of this technique in the field of plant research has rapidly developed (Casson et al 2005, Deng et al 2014, Cao et al 2017.…”
mentioning
confidence: 99%